The impact of new media towards teenagers in Malaysia / Abdul Rauf Ridzuan … [et al.] - Ridzuan, Abdul Rauf; Yusof, Fatin Nabihah; Ab Ghani, Siti Nur Farrah Faadiah; Siswantini, Siswantini; Abdul Halim, Nurul Ashikin (Faculty of Communication & Media Studies, 2022)
New media is a new platform for teenagers to participate in communicating with other people. The invention of technologies has made a change towards the use of media including political and economic as well. However, the usage of new media can be both in a positive and negative impacts respectively while it is a common use of new media by the teenagers nowadays. The purpose of this research is to identify the impact of new media towards teenager’s in Malaysia. This study is to identify the impact of new media which is the impact will be towards lack of communication, easily influenced and the spread of fake news. In conducting research, the researcher used Statistical Package of Social Science (SPSS) to measure the data. There are various methods and analysis are used to analyse the data collected from the questionnaires.